Basic Cell Culture Protocols - Pollard, Jeffrey W.; Pollard, Jeffrey W.; Walker, John M.; Walker, John M. (Methods in Molecular Biology,, 1997)
Now completely revised and updated from the original, much-acclaimed and bestselling first edition, Basic Cell Culture Protocols, 2nd ed. offers today's most comprehensive collection of easy-to-follow, cutting-edge protocols for the culture of a wide range of animal cells. Its distinguished contributors-often the perfectors of the detailed techniques being described-provide explicit, step-by-step instructions, along with extensive notes and tips that allow both experts and beginners to successfully achieve their desired results. Topics range from basic culture methodology to strategies for culturing previously uncultured cell types and hard-to-culture differentiated cells. Methods are also provided for the analysis of living cells by FACS, video microscopy, and confocal microscopy. Basic Cell Culture Protocols, 2nd ed. will surely follow in the footsteps of the first edition and, in the words of the reviewers, prove a still more "clear, easy-to-use well-sourced, and precise" work that belongs "in every cell culture laboratory.".